Expanded CAG/CTG repeats resist gene silencing mediated by targeted epigenome editing. Issue 3 (7th September 2021) - Yang, Bin; Borgeaud, Alicia C; Buřičová, Marcela; Aeschbach, Lorène; Rodríguez-Lima, Oscar; Ruiz Buendía, Gustavo A; Cinesi, Cinzia; Taylor, Alysha S; Baubec, Tuncay; Dion, Vincent
Abstract: Expanded CAG/CTG repeat disorders affect over 1 in 2500 individuals worldwide. Potential therapeutic avenues include gene silencing and modulation of repeat instability. However, there are major mechanistic gaps in our understanding of these processes, which prevent the rational design of an efficient treatment. To address this, we developed a novel system, ParB/ANCHOR-mediated Inducible Targeting (PInT), in which any protein can be recruited at will to a GFP reporter containing an expanded CAG/CTG repeat. Previous studies have implicated the histone deacetylase HDAC5 and the DNA methyltransferase DNMT1 as modulators of repeat instability via mechanisms that are not fully understood. Using PInT, we found no evidence that HDAC5 or DNMT1 modulate repeat instability upon targeting to the expanded repeat, suggesting that their effect is independent of local chromatin structure. Unexpectedly, we found that expanded CAG/CTG repeats reduce the effectiveness of gene silencing mediated by targeting HDAC5 and DNMT1. The repeat-length effect in gene silencing by HDAC5 was abolished by a small molecule inhibitor of HDAC3. Our results have important implications on the design of epigenome editing approaches for expanded CAG/CTG repeat disorders. PInT is a versatile synthetic system to study the effect of any sequence of interest on epigenome editing.